2014
DOI: 10.1021/es503574z
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Elimination, and Biotransformation of 17α-Ethinylestradiol by the Freshwater Alga Desmodesmus subspicatus

Abstract: Bioconcentration and transformation of the potent and persistent xeno-estrogen 17α-ethinylestradiol (EE2) by organisms at the basis of the food web have received only little research attention. In this study, uptake, elimination, and biotransformation of radiolabeled EE2 ((14)C-EE2) by the freshwater green alga Desmodesmus subspicatus were investigated. The alga highly incorporated radioactivity following (14)C-EE2 exposure. Up to 68% of the test compound was removed from the medium by D. subspicatus within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In a stream receiving wastewater effluent discharge, triclosan and triclocarban have been found able to bioaccumulate in filamentous algae with estimated bioaccumulation factors up to 2100 and 2700, respectively (Coogan et al 2007). Maes et al (2014) studied the removal of EE2 by Desmodesmus subspicatus and found EE2 can be taken up and biotransformed in algal cells and the ratio of EE2 between algae and water reached a maximum value of 2700 L kg -1 (Dry weight) after 24 h.…”
Section: Sorptionmentioning
confidence: 99%
“…In a stream receiving wastewater effluent discharge, triclosan and triclocarban have been found able to bioaccumulate in filamentous algae with estimated bioaccumulation factors up to 2100 and 2700, respectively (Coogan et al 2007). Maes et al (2014) studied the removal of EE2 by Desmodesmus subspicatus and found EE2 can be taken up and biotransformed in algal cells and the ratio of EE2 between algae and water reached a maximum value of 2700 L kg -1 (Dry weight) after 24 h.…”
Section: Sorptionmentioning
confidence: 99%
“…Such as for fungi, pollutant degradation by algae seems to involve intracellular and extracellular enzymatic systems (Figure 3). Intracellular degradation of pharmaceuticals involves a phase I enzyme (cytochrome P450) [163,[168][169][170][171][172][173] and a phase II enzyme (e.g., glutathione-S-transferases) [171]. Extracellular degradation of pharmaceuticals involves the excretion of various extracellular polymeric substances, such as polysaccharides, protein, enzymes, substituents (polysaccharide-link methyl and acetyl groups), and lipids to their surrounding environment.…”
Section: Mechanisms Of Removalmentioning
confidence: 99%
“…Some algae strains found in the literature [64,133,148,164,166,[168][169][170][176][177][178][179][180][182][183][184][185][186][187][188][189][190][191][192][193][194] proved to be effective in pharmaceutical removal (Table 1). Laboratory-scale batch assays [190] Biodegradation Laboratory-scale batch assays [191] Salicylic acid or paracetamol Pharmaceutical industry wastewater Algae…”
Section: Concluding Remarks and Future Challengesmentioning
confidence: 99%
“…During microalgae/duckweed cultivation estrogens are converted from one form into another; E1, E2 and EE2 can be interconverted rapidly, during a few hours of cultivation, while estrone (E1) is transformed into estriol and after an extended period (> 7 days) is further degraded into unknown lipophilic products (Lai et al, 2002;Shi et al, 2010;Zhang et al, 2014c). Among the removal mechanisms, it was shown that photodegradation and direct oxidation accounted for a small fraction of the total estrogen removal (Maes et al, 2014;Shi et al, 2010;Zhang et al, 2014c). On the other hand, even as the final removal of total estrogen can reach over than 85%, it was shown that the estrogenic activity of the medium was not reduced suggesting that the degradation products displayed the same or higher estrogenic activity compared to the parent compounds (Zhang et al, 2014c).…”
Section: Steroid Estrogensmentioning
confidence: 99%
“…The degree of intracellular concentration of estrogen has not yet been extensively investigated; however, it was shown that the microalga Desmodesmus subspicatus incorporated around 23% EE2 from its surrounding medium after 24 h, with no further uptake. After re-incubation of contaminated cells in clean medium a portion of EE2 was desorbed, but 30% of the initially incorporated estrogen remained in the microalgal biomass (Maes et al, 2014), suggesting, at least partially, a gradient driven adsorption onto cell surfaces.…”
Section: Steroid Estrogensmentioning
confidence: 99%